Serum Klotho protein level in type 2 diabetic patients depending on the renal function - I. Topchii; P. Semenovykh; T. Shcherban; V. Galchinska; K. Savicheva (Ukrainian Journal of Nephrology and Dialysis, 2020)
The study aimed to assess serum Klotho protein level in type 2 diabetic patients depending on kidney function.Methods. This observational study included 72 patients with diabetes mellitus (DM) and 26 patients with acute coronary syndrome. The control group consisted of 20 healthy subjects. Depending on the presence of albuminuria and glomerular filtration rate (GFR), the diabetics were divided into the following groups: group I included the patients with normal GFR and without albuminuria (n = 25); group ІІ consisted the patients with normal GFR and albuminuria (n = 23); group III – the patients with reduced GFR and albuminuria (n = 24) and group ІV included the patients with acute coronary syndrome (n = 26).The GFR was calculated using the CKD EPI formula (KDIGO 2012). The concentration of Klotho protein was determined by enzyme-linked immunosorbent assay.Results. The development of diabetic nephropathy in type 2 diabetic patients accompanied by a significant decrease of soluble Klotho compared with the controls and the patients of the1-st group. The level of Klotho protein in the group of patients with albuminuria decreased to (490.66 ± 58.76) pg/ml (p <0.05). The lowest concentration of Klotho (443.58 ± 46.92) pg/ml was found in the advanced stages of diabetic nephropathy, namely in patients with albuminuria and impaired renal function. Moreover, a significantly decreased serum Klotho was observed in acute coronary syndrome group in comparison with the control group (p <0.05). There were inverse correlations of Klotho concentration with urinary albumin and blood creatinine levels and a direct correlation between Klotho and GFR.Conclusions. The obtained data indicated the key role of Klotho protein in the formation of renal pathology in type 2 diabetes and the feasibility of practical use of Klotho determination as an early diagnostic marker of renal disorders and cardiovascular risk assessment. The strategies improving Klotho production may be useful in the reduction of both renal and vascular lesions progression in type 2 diabetic patients.